1984
DOI: 10.1172/jci111458
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen metabolites stimulate thromboxane production and vasoconstriction in isolated saline-perfused rabbit lungs.

Abstract: Abstract. Generation of reactive oxygen metabolites, thromboxane increases, and vasoconstriction have been implicated in the pathogenesis of acute edematous lung injury, such as that seen in patients with the Adult Respiratory Distress Syndrome (ARDS), but their interactions are unknown. We hypothesized that reactive 02 products would stimulate arachidonic acid metabolism in lungs and that vasoactive products of arachidonate, such as the potent vasoconstrictor thromboxane A2, might then mediate 02-metabolite-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(71 citation statements)
references
References 31 publications
3
67
0
1
Order By: Relevance
“…Our results are consistent with earlier observations (16,29). In these studies, catalase completely blocked the pulmonary vasoconstriction induced by XO.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are consistent with earlier observations (16,29). In these studies, catalase completely blocked the pulmonary vasoconstriction induced by XO.…”
Section: Discussionsupporting
confidence: 94%
“…Our observation is in agreement with the work of Tate et al (16) who found increased mean pulmonary artery perfusion pressure induced by 0 2 metabolites in isolated rabbit lungs. This group showed that the pressure augmentation was induced by thromboxane generation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Alternatively, increased production of vasoconstrictor arachidonate metabolites (e.g. thromboxane A2 or leukotrienes) potentiated by 0, metabolites may be etiologic to late hypoperfusion (37,38). The other attractive explanation for decreased CBF at 1-4 h PA is that OFR damage cerebral vessels causing a vasoconstricted state.…”
Section: Discussionmentioning
confidence: 99%
“…This is associated, however, with a pronounced concomitant increase of superoxide anion production [101]. These anions inactivate NO and furthermore, they interact with NO leading to production of peroxynitrite [102,103], a potent oxidant, which in turn stimulates cyclooxygenase catalysis, lipid peroxidation and increased prostanoid production resulting in endothelial dysfunction [104,105]. Superoxide dismutase, a scavenger of superoxide anion, has been shown to normalise NO-mediated vasorelaxation impaired by increased glucose concentrations [98,106,107].…”
Section: Role Of Free Radicalsmentioning
confidence: 99%